Virtual reality art as an innovative Buddhist learning tool. (4th February 2022) - Karnchanapayap, Gomesh; Chaetnalao, Atithep
From paintings, sculptures, print, to digital media, art and technology have always been integral elements used to create Buddhist learning tools since ancient times. With the rise of virtual reality mass acceptance, the new art form can innovatively be developed as an effective Buddhist learning tool. The VR artworks from this research are the results of merging technological advancements and art with the Buddhist faith to construct a ground-breaking Buddhist learning tool. The artworks enable multi-level learning experience for the audience. First, learning by sensory perceptions within VR makes the audience 'remember' things. Second, learning by simulated experiences enables the audience to 'know' by being in the events. Finally, learning by purposefully creating within the virtual world empowers the audience to 'understand' the core philosophy of the artworks. This learning innovation is not only an effective learning tool but also suitable for new generations as a new medium to pass on the faith of Buddhism.